2015
DOI: 10.1146/annurev-nutr-071714-034347
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E: A Role in Signal Transduction

Abstract: Vitamin E modulates the activity of several signal transduction enzymes with consequent alterations of gene expression. At the molecular level, vitamin E may directly bind to these enzymes and compete with their substrates, or it may change their activity by redox regulation. The translocation of several of these enzymes to the plasma membrane is regulated by vitamin E, suggesting the modulation of protein-membrane interactions as a common mechanism for vitamin E action. Enzyme-membrane interactions can be aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 276 publications
(367 reference statements)
0
88
0
3
Order By: Relevance
“…These data support the hypothesis that the protective effect of α-tocopherol does not depend on the cell type considered, whereas the protective effect of γ-tocopherol is cell-type specific. As Trolox, which is a strong antioxidant, provided no protection against the toxic effects of 7KC, our data suggest that the anti-oxidative properties of α- and γ-tocopherol are not essential to prevent these toxic effects of 7KC, and that the protective activities of these tocopherols involve other mechanisms [38,39,40,77]. Our observations are in agreement with data reporting that all of the stereoisomers and derivatives of Vitamin E have antioxidant activities and that small differences exist for each form [38,39,78].…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…These data support the hypothesis that the protective effect of α-tocopherol does not depend on the cell type considered, whereas the protective effect of γ-tocopherol is cell-type specific. As Trolox, which is a strong antioxidant, provided no protection against the toxic effects of 7KC, our data suggest that the anti-oxidative properties of α- and γ-tocopherol are not essential to prevent these toxic effects of 7KC, and that the protective activities of these tocopherols involve other mechanisms [38,39,40,77]. Our observations are in agreement with data reporting that all of the stereoisomers and derivatives of Vitamin E have antioxidant activities and that small differences exist for each form [38,39,78].…”
Section: Resultsmentioning
confidence: 91%
“…This demonstrates that molecules able to prevent the toxic effects of 7KC can be active by involving mechanisms other than those associated with their antioxidant power. With tocopherols, several mechanisms are also probably involved: (i) impairment of 7KC accumulation in lipid rafts [34,41]; (ii) changes in the surface exposure of membrane receptors; and (iii) modulation of signal transduction by modifying plasma membrane properties [77,86]. Moreover, as it has been reported that the cytoprotective properties of α-tocopherol are mostly related to gene regulation rather than to antioxidant activity in toxin-induced cell death in hepatocytes [87], similar mechanisms cannot be excluded in the ability of tocopherols to prevent the toxic effects of 7KC.…”
Section: Resultsmentioning
confidence: 99%
“…It acts as a chain-breaking antioxidant, especially against peroxyl radicals, and is thus essential in maintaining the integrity of long-chain polyunsaturated fatty acids found in cell membranes (9). Recently, it has been shown to also exert non-antioxidant activities (10): modulation of gene expression (11,12), inhibition of cell proliferation (13), regulation of bone mass (14)… Since oxidative stress has been implicated in the aetiology of several diseases, e.g. cardiovascular diseases and cancers, numerous epidemiological studies have investigated the association between VE dietary intake or status (usually evaluated as the fasting blood -tocopherol concentration) and the incidence of these diseases and reported negative associations (15)(16)(17).…”
Section: Stereoisomers (Rrr Rrs Rsr Rss Srr Srs Ssr Sss)mentioning
confidence: 99%
“…For instance, vitamin C, beyond its celebrated antioxidant activity, has been implicated as cofactor in several metabolic pathways, such as the synthesis of noradrenaline and carnitine, the post-translational modification of collagen, the catabolism of tyrosine, the calcium management in bones and a wide spectrum of immune-related processes [45,46,47,48]. Likewise, vitamin E exerts many non-antioxidants activities (predominately the α-tocopherol isoform) including modulation of gene expression, inhibition of smooth muscle cell proliferation, preservation of endothelial integrity as well as inhibition of platelet and monocyte-endothelial adhesion [49,50,51,52,53]. On this basis, a challenging question is whether the outcomes of a combined "antioxidant" intervention with vitamins C and E are mediated by their redox or non-redox properties.…”
Section: The Non-antioxidant Effects Of Antioxidantsmentioning
confidence: 99%